DEMOCRATIC EDUCATION IN “MERDEKA BELAJAR” ERA - Khanif Maksum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2021)
Educational Democracy is a view of life that prioritizes equal rights and obligations as well as an equal treatment between educators and students in the learning process. Democracy in education contains elements of independence, freedom, and responsibility. An independent attitude to develop self-confidence and to be aware of one's limitations is very important to foster awareness that life in the community requires collaboration with other individuals. Freedom is defined as a life purpose that rests on the awareness of social pluralism, not solely on the interests of individuals or groups. Therefore freedom itself must be accompanied by a sense of full responsibility. The word